Diversity of fragments in the collapse of brittle solids - Brito, V. P.; Gomes, M. A. F.; Souza, F. A. O.; Adhikari, Sadhan K. [UNESP] (Elsevier, 1998)
An experimental study of fragmentation of brittle solids under the application of repeated impulsive force is made, emphasizing the behavior of the diversity of fragments. Several scaling relations involving diversity and number of fragments are obtained from experiments and the results are compared with computer simulations. © 1998 Elsevier Science B.V. All rights reserved.
Keywords: Brittle solids; Collapse; Diversity; Fragmentation; Brittleness; Statistical mechanics; Solid state physics